AB0391 EFFECT OF HCQ ON LLDAS ACHIEVEMENT IN SLE PATIENTS. (2nd June 2020) - Wakiya, R.; Ueeda, K.; Shimada, H.; Nakashima, S.; Mahmoud Fahmy Mansour, M.; Kato, M.; Miyagi, T.; Ushio, Y.; Sugihara, K.; Kameda, T.; Dobashi, H.
Abstract : Background: HCQ for SLE in Japan has been administered in many cases after approval. Therefore, the effect of additional administration of HCQ on low disease activity of SLE was considered to be clearer. Objectives: To clarify the effect of HCQ treatment on the control of disease activity in SLE patients. Methods: All SLE patients with low disease activity (LDA) enrolled in this study started additional HCQ treatment from January 2016. All patients with LDA enrolled in this study started HCQ treatment and had been receiving oral HCQ continuously for at least 3 months without using other immunosuppressive treatments or glucocorticoids. Disease activity was evaluated by SLEDAI, CLASI, and LLDAS, and serum complement values, anti-DNA antibodies, and pro-inflammatory cytokines were analyzed as immunological biomarkers before and after HCQ treatment. Results: 52 of 100 patients were enrolled in this study (M:F; 4:48, average age; 40.6±13.4). 24 lupus nephritis patients were in sustained remission. 29 patients (56%) achieved LLDAS and 3 patients (6%) achieved clinical remission (CR) before HCQ administration. Of the 20 patients (38%) who did not achieve LLDAS before HCQ administration, the LLDAS achievement rates at 3, 6, and 12 months after additional HCQ were 47%, 59%, and 81% (including 12.5% of CR achievement rates), respectively. Serum levels of MRP8, MRP14, TNF-α, IL-6, VEGF-A, IL-1ra, MIP-1a and IL-2 decreased significantly 3 months after additional HCQ treatment. In addition, serum levels of MRP8, MRP14, TNF-α, IL-6 and IL-2 also decreased significantly 3 months after additional HCQ treatment despite achieving LLDAS or CR. The expressions of IFN-α didn't decrease significantly in 9 cases that could be detected. The magnitude of the changes in serum MRP8, MRP14, IL-8 and Il-1ra levels in patients with a history of LN was significantly higher than in those without a history of LN. The magnitude of the reduction in serum MCP-1 levels in patients not achieving LLDAS with a history of LN was significantly higher than in those without a history of LN(p=0.046). The change of CLASI activity score was correlated with the change in serum levels of MRP14 and MCP-1 with univariate analysis (MRP14: r=-0.41, p=0.017, MCP-1: r=-0.58, p=0.0006). The change of serum C3 levels had a negative correlation with MCP-1(r=-0.33, p=0.022). The magnitude of the change in serum levels of MRP14, TNF-α, IL-8, MCP-1, MIP-1a and IL-1ra in patients achieving LLDAS were correlated with the change of CLASI activity score with univariate analysis (MRP14: r=-0.49, p=0.041, TNFα: r=0.74, p=0.0038, IL-1ra: r=0.66, p=0.038, MIP-1a: r=0.63, p=0.037, Figure 1 ). Moreover, the change of serum C3 and C4 levels in them had a negative correlation with the change of serum MCP-1 levels (Figure 2 ). Conclusion: Additional administration of HCQ is useful for cytokine control even in LLDAS-achieved cases, and particularly contributes to the improvement of skin lesion. In addition, regulation of IL-8 and MCP-1 is important for control of renal lesions of SLE, and more control of the activity of SLE The effect of HCQ on IL-8 and MCP-1 is related to the control of renal lesions in SLE, so that disease activity of more SLE patients might be more controlled disease activity. References: [1]R Wakiya, et al. Hydroxychloroquine modulates elevated expression of S100 proteins in systemic lupus erythematosus. Lupus. 2019;28:826-833 Disclosure of Interests: None declared